Financial service supply with potential for supporting climate-smart agriculture - Wattel, Cor; Asseldonk, Marcel van (2018)
Climate-smart agriculture (CSA) requires new business models, as well as adapted financial services and incentives, in order to scale out. The present study makes an inventory of the financial services available around the Climate-Smart Village AR4D project sites of CCAFS in 20 countries. Based on web sources, it maps the most relevant financial service providers, in terms of geographical proximity, affinity to agriculture, smallholders and SMEs, and scale of operations. The study shows that some countries and project sites enjoy a reasonably wide range of financial services and providers that could be relevant for CSA scaling. Other sites however are more remote and distant from financial service providers. In a next phase of the project, case studies will be identified for further research into business models and financial services and incentives for CSA.